Training the Algorithm: Governance, Agency, and Literacy in the Use of YouTube - Sued, Gabriela Elisa (2022)
This study addresses the experiences of young Mexican users with YouTube’s recommendation algorithms. It seeks to determine if they are subordinated to algorithmic governance or if, on the contrary, they are capable of developing some tactics to resist algorithmic power through their agency. It uses a qualitative methodology based on focus groups and shows that users are not entirely subordinated to the platforms. Their possibilities of agency vary depending on the different technological appropriations of the platform, the intuitive theories about the ways in which these operate, the ability to dodge algorithmic distortions, and the resources to evaluate the quality of the information offered. As a result, the study identifies the specific skills that constitute algorithmic literacy.